Persepsi Jamaah Mengenai Fasilitas dan Biaya dalam Memilih Jasa Umroh - Nurali Agus Najibul Zamzam; Udik Jatmiko (Jurnal Ilmu Manajemen Advantage, 2019)
This research aims to analyze and determine the effect of the facilities and costs of umrah travel on the choosing decision PT Uda CS Holidays Indonesia both partially and simultaneously. The population in this study is 612 pilgrims using non probability sampling techniques with accidental sampling as the approach. The data analysis techniques used are: (1) Validity and Reliability test, (2) Multiple Linear Regression Analysis, (3) F Test Analysis, (4) T-Test, and (5) Determinant Coefficient Test. The result of data analysis can be concluded as follows: (1) There is no partial positive and significant effect between the umrah facility variable on the choosing decision the Umrah package at PT Uda CS Holidays Indonesia (2) There is a positive and significant effect partially between the variable costs of umrah travel on the choosing decision Umrah package at PT Uda CS Holidays Indonesia. (3) Umrah facilities and the cost of joint umrah arrangements have a positive and significant effect on the choosing decision the Umrah package at PT. Uda CS Holidays Indonesia